Hubungan antara Andropause dengan Disfungsi Ereksi pada Pria di Kecamatan Jebres, Surakarta - Rr Vita Aprilina Prastiti; Rosalia Sri Hidayati; Slamet Riyadi (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: Andropause is used to describe the decline of testosterone in males which is a part of aging in males and affects many health parameters. Erectile dysfunction is a consistent or recurrent inability in males to attain and/or maintain a penile erection sufficient for sexual activity. Decreased testosterone levels can lead to physical and sexual performance in males slowly degenerate. This research aims to know the association between andropause and erectile dysfunction in males at Jebres, Surakarta. Methods: This research used a non-experimental analytical study using cross sectional approach that was done at Jebres, Surakarta on June 2014. The subjects of the research were males at Jebres, Surakarta chosen with a purposive random sampling technique. The size of the samples was 60 males according to the inclusion and exclusion criteria that had been set previously. Independent variable in this research was andropause while the dependent variable was erectile dysfunction. Respondents collected data from questionnaires. The collected data were analyzed with Chi-Square test, which was followed by using Contingency coefficient test to determine how closely the relationship of these two variables. Results: There was a significant association in the proportion of andropause among males with and without erectile dysfunction in Jebres population, Surakarta (p = 0.000; Cc = 0.444). Conclusions: There is an association between andropause and erectile dysfunction in males at Jebres, Surakarta. Keywords: Andropause, Erectile Dysfunction, Males, Surakarta